1992
DOI: 10.1038/bjc.1992.347
|View full text |Cite
|
Sign up to set email alerts
|

c-erbB-2 positive breast tumours behave more aggressively in the first years after diagnosis

Abstract: SummaryIn a retrospective study the expression of the c-erbB-2 oncogene was determined immunohistochemically in 276 breast cancer samples from 253 patients with the antibody 21N. The follow-up period was between 7 and 12 years. This study showed a trend for an inverse relationship between c-erbB-2 positive tumours and estrogen receptors (ER). A correlation was assessed between c-erbB-2 positive tumours and histological grade, liver metastases as first site of metastases, disease free survival time (DFS) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…A strong negative association between neu-overexpression and oestrogen or progesteron receptor status has also been described [41,65,89]. The fact that most neuoverexpressing turnouts lack steroid receptors can be explained on the one hand by the repressed expression of the neu-protein during oestrogen-induced proliferation and on the other by its enhanced expression during growth arrest and/or differentiation of mammary cells.…”
Section: The Neu-protein and Prognosis Of Breast Cancermentioning
confidence: 90%
See 2 more Smart Citations
“…A strong negative association between neu-overexpression and oestrogen or progesteron receptor status has also been described [41,65,89]. The fact that most neuoverexpressing turnouts lack steroid receptors can be explained on the one hand by the repressed expression of the neu-protein during oestrogen-induced proliferation and on the other by its enhanced expression during growth arrest and/or differentiation of mammary cells.…”
Section: The Neu-protein and Prognosis Of Breast Cancermentioning
confidence: 90%
“…In some multivariate analyses neu-overexpression retained its prognostic significance, being second to the classical prognostic indicators in breast cancer such as the number of invaded axillary lymph nodes, tumour size, turnout differentiation and receptor status [30,75). According to some investigators, neu-overexpressing tumours seem to behave worse particularly the first years after diagnosis [19,75], and these patients suffer from a shorter disease free survival time and shorter overall survival time between the 3rd and 4th year after diagnosis [65,75]. The difference in prognosis seems to vanish from the 5th year after diagnosis.…”
Section: The Neu-protein and Prognosis Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about its biological function would provide insight into its role in human breast cancer. It may also generate novel data on the biology of breast cancer, since p185 erbn2 is overexpressed in about 20% of the breast cancers [24]. Because of its prognostic value [7], the inununolabeling for p185 erba2 is performed more and more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Other similar studies have also demonstrated no relationship between c-erbB-2 positivity and age. 11,15 It has been shown that oestrogen receptorpositive patients have a longer 5-year DFS rate than oestrogen receptor-negative A Gurkan, G Erdogan, O Erdogan et al Expression of c-erbB-2 and p53 in breast carcinoma patients patients; the difference was between 5% and 10%, and no differences were seen with progesterone receptor status. 16 In the present study we did not find any relationship between hormone receptor status and disease relapse or DFS.…”
Section: A Gurkan G Erdogan O Erdogan Et Al Expression Of C-erbb-2mentioning
confidence: 99%